PREPOSISI DALAM PROVERBS - Ismail, Reynaldy; Pamantung, Rina P.; Pelealu, Hetty (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis research entitled â€œPrepositions in the Book of Proverbsâ€. It is to identify, classify, analyze, and describe the forms and the meanings of prepositions in the book of Proverbs. In analyzing the data, the writer used theory based on Aarts and Aarts theory (1982) to identifying classifying the forms of preposition and Marcella Frankâ€Ÿs theory (1972) in analyzing and describe the meaning of preposition as a part of descriptive method. The data were taken from the book of Proverbs. The form of prepositions that founded in the book of Proverbs, such as simple prepositions consist of : after, as, at, before, by, for, from, like, in, near, of, on, through, till, up and with, whereas complex prepositions consist of : because of, for the purpose of, in front of, out of, up down and up to. The meaning of prepositions that founded, consist of: time, place or position, direction, cause or reason, purpose, accompaniment, comparison, means, manner, in the capacity of, material, source, separation, apposition, characterized by, exception and example.Keywords: Prepositions, Forms and Meanings, The Book of Proverbs